Evaluasi dan Perbaikan Pada Antarmuka Pengguna Website Perusahaan Daerah Air Minum (PDAM) Kota Malang Dengan Menggunakan Metode Usability Testing dan Heuristic Evaluation - Lailatul Fitriyah; Satrio Hadi Wijoyo; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Regional Drinking Water Company (PDAM) Malang City is a drinking water provider company with one of its services through the website. The results of initial interviews with website managers and users indicate that there are problems, namely the display has not been developed, the user is confused about several features that are not suitable, one of which is the menu that has not been dropdown, login designation, and menus such as advertisements can affect the level of usability. So, it is necessary to evaluate the interface of the website by involving the natural point of view of users and experts to find problems and recommend improvements. This study uses usability testing and heuristic evaluation methods. Usability testing uses 3 measurement aspects, namely effectiveness, efficiency, and satisfaction. The heuristic evaluation uses 10 principles of Nielsen's heuristic utility. The results of usability testing found 14 interface problems and heuristic evaluation found 25 interface problems. Usability testing shows the measurement of effectiveness at the level of error that is low and the level of completion which is above average. Measurement of efficiency is high, and measurement of satisfaction is less satisfactory. Then, heuristic evaluation shows that the most interface problems are the H8 (aesthetic and minimalist design) principle. Based on the results of the evaluation, 30 recommendations were made using the guidelines for a better level of use.